Tuning the catalytic activity of a single Mo atom supported on graphene for nitrogen reduction via Se atom doping - Zhou, Hong Yu; Li, Jian Chen; Wen, Zi; Jiang, Qing (Physical chemistry chemical physics : PCCP, 2019)
Electrochemical nitrogen (N 2 ) fixation as an effective method has realized the sustainable production of ammonia where efficient electrocatalysts for converting N 2 into NH 3 at room temperature have become a key scientific issue. Herein, we proposed that the catalytic activity of a single Mo atom supported on graphene (Mo/G) for the nitrogen reduction reaction (NRR) can be tuned by non-metal heteroatom (B, N, P, S, Se etc. ) doping. Our density functional theory (DFT) calculations revealed that the Se atom is the best doping element to tune the optimal electronic structure of the Mo atom for catalyzing the NRR among these heteroatoms, leading to the lowest potential of 0.41 V vs. RHE for Mo/SeG, which is much better than the current metal-based catalysts. Our work provided a new strategy to design electrocatalysts for the NRR.